Analysis and design of hybrid systems 2006 : a proceedings volume from the 2nd IFAC Conference, 7-9 June, 2006, Alghero, Italy - ADHS 06 (2006 : Alghero, Italy); Cassandras, Christos G.; ScienceDirect eBooks (Oxford : Elsevier for International Federation of Automatic Control, 2006)
This volume contains the proceedings of ADHS06: the 2nd IFAC Conference on Analysis and Design of Hybrid Systems, organized in Alghero (Italy) on June 7-9, 2006. ADHS is a series of triennial meetings that aims to bring together researchers and practitioners with a background in control and computer science to provide a survey of the advances in the field of hybrid systems, and of their ability to take up the challenge of analysis, design and verification of efficient and reliable control systems. ADHS'06 is the second Conference of this series after ADHS'03 in Saint Malo. * 65 papers selected through careful reviewing process * Plenary lectures presented by three distinguished speakers * Featuring interesting new research topics.
Plenary Lectures -- Chattering Problem for Sliding Mode Control Systems -- (V. Utkin, H. Lee). -- Challenges and Opportunities for System Theory in Embedded Controller Design (A. Sangiovanni Vincentelli). -- Optimal Control in Hybrid Systems (C. Lung, P. Riedinger). -- Observers for Hybrid Systems. -- Continuous and Hybrid Petri Nets. -- Modeling and Simulation of Hybrid Systems. -- Control of Hybrid Systems 1. -- Structural Analysis and Approximation of Hybrid Systems (Invited). -- Control of Hybrid Systems 2. -- Stochastic Hybrid Systems. -- Controller Design Based on Hybrid Models of Industrial Plants (Invited). -- Diagnosis and Identification. -- Applications of Hybrid Control (Invited). -- Hybrid Simulation Tools: Principles, Challenges and Applications (Invited). -- Stability 1. -- Model Predictive Control. -- Stability 2.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Automatic control -- Congresses; Hybrid computers -- Congresses; TECHNOLOGY & ENGINEERING -- Automation; TECHNOLOGY & ENGINEERING -- Robotics; Automatic control; Hybrid computers; Hybrid systems; IFAC; Electronic books